CONTINUOUS-FLOW ENZYMATIC KINETIC RESOLUTION MEDIATED BY A LIPASE NANOBIOCONJUGATE - MOISĂ, Mădălina Elena; BENCZE, László Csaba; PAIZS, Csaba; TOȘA, Monica Ioana (Studia Universitatis Babeș-Bolyai Chemia, 2019)
This study describes the development of a continuous-flow procedure for the enzymatic kinetic resolution of rac-1-phenylethan-1-ol with the clickable acylating agent 2,2,2-trifluoroethyl 2-(prop-2-yn-1-yl-oxy)acetate, which allows facile click reaction-based downstream, enabling the large-scale chemo-enzymatic synthesis of both secondary alcohol stereoisomers with high enantiopurity. The influence of flow rate, acylating agent and substrate concentration upon the productivity of the packed-bed reactor was investigated. In addition to this, the performances of continuous-flow and batch reactors were compared.